Polygonal-Pyramidal Method of Structured Anatomical Analysis in Professional Art Education - Parkhomenko, Konstantin Alexandrovich (2024)
This article examines the author's method for teaching professional art education through the utilization of polygonal and geometric shapes. It delves into the fundamental principles, tools, and techniques involved in working with such forms. Academic Drawing, a cornerstone discipline in painting education, is explored within the context of this method. Specifically, the article discusses the Method of Anatomical Polygonal-Pyramidal Structured Analysis and Geometrical-Plastic Modeling of Form, implemented within the professional art education curriculum at the Lugansk State Academy of Culture and Arts, Russia, under the Faculty of Fine and Applied Arts, Department of Easel Painting. To assess the method's effectiveness, a study employing the stratometric modeling method was conducted with five student study groups, comprising female students aged 18-25, all pursuing training in Stationary Painting. The study spanned various periods, revealing the method's capacity to expedite professional development and yield significant student achievements. The article concludes by underscoring the method's importance in nurturing spatial-artistic thinking, rooted in the identification of anatomical nodes influencing overall figure structure and internal plasticity. By connecting these nodes into a cohesive system, the method facilitates the expression of artistic constructive form. Through the transformation of triangles into volumetric geometric forms and their layered application, the method enables the creation of tonal gradations and overall figure volume. Moreover, it cultivates anatomical constructive thinking, enhances understanding of human structure, and fosters proficiency in applying mathematical principles to creative problem-solving.